A Novel Rapid Temperature Swing Adsorption Post-combustion CO2 Capture Process Using a Sorbent Polymer Composite. (July 2017) - Berger, Adam H.; Horowitz, Jason A.; Machalek, Tom; Wang, Andrew; Bhown, Abhoyjit S.
Abstract: A novel material and process for post-combustion CO2 capture using solid sorbents is described. The material can house solid sorbents in a hydrophobic polymer allowing the use of direct steam inject for bed regeneration direct cooling water injection for cooling and bed conditioning. The process description, results from characterization of these materials, and process analysis are presented.